Processed ship-based Multibeam Sonar Images from the Amundsen Sea, Antarctica acquired during the R/V Nathaniel B. Palmer expedition NBP0702 (2007) (IEDA: Marine-Geo Digital Library, 2007)
This data set was acquired with a ship-based Kongsberg EM120 Multibeam Sonar system during R/V Nathaniel B. Palmer expedition NBP0702 conducted in 2007 (Chief Scientist: Dr. Stan Jacobs; Investigator: Dr. Frank Nitsche). These data files are of PDF format and include Bathymetry images that have been processed. Data were acquired as part of the project: The Amundsen Continental Shelf and the Antarctic Ice Sheet, and funding was provided by NSF grant: ANT04-40775.